Sunteți pe pagina 1din 2

# 2.3 2.3.

## LINEAR EQUATION Definition: A first-order differential equation of the form

a1 ( x) dy + a0 ( x) y = g ( x) dx (1)

is said to be a linear equation in the dependent variable y . Note: The equation in (1) fulfills the three characteristics of a linear equation as discussed in section 1.1. 2.3.2 If g ( x) = 0 , the equation in (1) is said to be a first-order homogeneous linear differential equation. Example, xy + y = 0 .
If g ( x) 0 , the equation in (1) is said to be a first-order nonhomogeneous linear differential equation. Example, xy + y = e x . 2.3.3

## Standard form of a first-order linear differential equation

Divide both sides of (1) by the leading coefficient, a1 ( x) , so that the coefficient of dy is one. dx dy a0 ( x) g ( x) + y= (2) dx a1 ( x) a1 ( x)

Let

## a0 ( x) g ( x) = p ( x) and let = f ( x) . Then (2) can be written as (3). a1 ( x) a1 ( x) dy + p ( x) y = f ( x ) dx (3)

Equation (3) is known as the standard form of a first-order linear differential equation.

1

2.3.4

## Method for solving a linear first-order differential equation

(i) Check to make sure that the linear equation is in the standard form as given in (3). (ii) Identify p ( x) and evaluate the integrating factor (IF), IF = e (iii)Multiply each side of (3) by the IF, as given in (4) e
p ( x ) dx p ( x ) dx dy p ( x ) dx p( x) y = e f ( x) +e dx

p ( x ) dx

(4)

The left hand side of (4) is automatically the derivative of the IF and the dependent variable y , that is,
p ( x ) dx d p ( x ) dx e y = e f ( x) dx

(5)

(iv) Integrate both sides of Equation (5) and solve for y to obtain the general solution of the given differential equation. (The general solution is the most general form that the solution can take and does not take into account any initial conditions). 2.3.5

Constant of integration
It is unnecessary to include the constant of integration, c , when evaluating the indefinite p ( x ) dx . The constant of integration will be eventually cancelled at integral in the IF = e some point during the process of the solution. Hence, disregard the constant.

2.3.6

Exercises:
(a) Find the general solution of the given differential equation. (i) x dy 4 y = x6e x dx Ans: Ans: y = x5 e x x 4 e x + cx 4

(ii) ( x + 1) y + ( x + 2) y = 2 xe x (b) Solve the given initial-value problem. (i) ( x + 1) dy + y = ln x , y (1) = 10 dx (ii) y + (tan x) y = sin 2 x , y (0) = 1

y=

x2 c + x x e ( x + 1) e ( x + 1)

Ans: Ans:

x ln x x 21 + ( x + 1) ( x + 1) ( x + 1) y = 2 cos 2 x + 3cos x y=
2